PEMBERIAN TEKNIK MULLIGAN DAN SOFT TISSUE MOBILIZATION LEBIH BAIK DARIPADA HANYA SOFT TISSUE MOBILIZATION DALAM MENINGKATKAN LINGKUP GERAK SENDI EKSTENSI, ROTASI, LATERAL FLEKSI CERVICAL PADA MECHANICAL NECK PAIN - -, sudaryanto; Sutjana, Dewa Putu; Irfan, Muhammad (Sport and Fitness Journal; Volume 1, No.2, 2013)
Mechanical neck pain has the same high prevalence with low back pain, and commonly found in many of physiotherapy practice. Combination of Mulligan technique and Soft Tissue Mobilization are one of manual therapy technique highly effective and efficient to care the case of mechanical neck pain but still very rarely used by physiotherapist in fields of practice. This study aimed to know the effectiveness between Mulligan technique – Soft Tissue Mobilization and only Soft Tissue Mobilization to the increasing range of motion extension, rotation and side flexion cervical on the mechanical neck pain. The study design was a pre test – post test control group design using two group of samples are control groups that given intervention Soft Tissue Mobilization and treatment groups that given a combination of Mulligan technique and Soft Tissue Mobilization. Measuring instrument used for data collection was goniometer, that the goniometer was used to measure the range of motion extension, rotation and lateral flexion of the cervical either before the intervention and after the intervention. Sample of this study was 32 people who divided into 2 groups of samples were 16 people in the control group and 16 people in the treatment group. Samples in the control group had a mean age of 35,69 with male of 7 people (43,8%) and female of 9 people (56,2%) as well as limitations of the right direction were 12 people (75%) and left direction were 4 people (25%). Whereas in the treatment group had e mean age of 35,94 with male of 10 people (62,5%) and female of 6 people (37,5%) as well as limitations of the right direction were 11 people (62,5%) and left direction were 5 people (31,2%). The results of hypothesis testing using independent sampel t-test showed a significant difference between the mean post-intervention ROM extension, rotation, lateral flexion of the control groups and the mean post-intervention ROM extension, rotation, lateral flexion of the treatment groups, with value p < 0,05. It is suggests that the Mulligan technique and Soft Tissue Mobilization resulting increase range of motion extension, rotation, and side flexion of the cervical that significantly greater than only Soft Tissue Mobilization on the mechanical neck pain. Thus, it can be concluded that the Mulligan technique and Soft Tissue Mobilization better than only Soft Tissue Mobilization to the increasing range of motion extension, rotation, and side flexion cervical on the mechanical neck pain.
Keywords: Mechanical Neck Pain, Mulligan Technique, Soft Tissue Mobilization